Village Development Inequality in Indonesia: Mapping the Influence of Human Capital and Village Funds - Lukman Hakim; Muhammad Rizaldi; Agus Suman; Marlina Ekawaty; Akmal Riza; Nasywa Zhahirah (SCAD Independent, 2026)
Village-level development disparities remain a persistent challenge in Indonesia's broader economic progress. This study aimed to map and analyze regional disparities in village development across 33 provinces in Indonesia from 2018 to 2022, using the Village Development Index (VDI) as a proxy. Employing descriptive statistical analysis and spatial mapping, the study examined the roles of two key factors: human capital, measured by the Human Development Index (HDI), and fiscal transfers, proxied by the Village Fund. The findings revealed that provinces in Java generally achieved higher VDI scores compared to those outside Java, with Bali as a notable exception. The disparities were influenced by the quality of human resources, accessibility to basic services, proximity to economic centers, and the effectiveness of Village Fund management. The study underscored the importance of strengthening human capital, improving governance in fund allocation, and addressing structural inequalities to promote more equitable and sustainable village development. These insights offer valuable implications for national policy and contribute to broader discussions on inclusive development strategies in emerging economies.